Orthopedic Surgery and Flight Surgery: Income Differences Between the Navy Health Professions Scholarship Program and Civilian Orthopedic Surgery. Issue 11 (30th December 2020) - Goodrich, Eric; Goodrich, Richard P
Abstract: Introduction: The purpose of this study to analyze the financial impact of choosing a civilian or military orthopedic surgery career. It will examine the most common scenarios to become an orthopedic surgeon in the Navy Health Professions Scholarship Program to include becoming a flight surgeon. To the authors' knowledge, there is no peer-reviewed literature that financially analyzes the most common scenarios for a Navy Health Professions Scholarship Program scholarship recipient to become an orthopedic surgeon. Materials and Methods: Salaries for Navy orthopedic surgeons, residents, and flight surgeons were recorded using the 2020 Defense Finance and Accounting Service pay tables and Navy Fiscal Year 2019 Medical Corps Special Pay Guidance. The median income of civilian orthopedic surgeons was recorded using Salary.com . The present value (PV) and future value (FV) were calculated using the Consumer Price Index-U and average Department of Defense pay increases over the past 20 years. Six common scenarios were utilized to calculate the PV and FV of civilian compared to Navy orthopedic surgeons. Results: The two highest earning net FVs among all Navy scenarios were those surgeons who kept their Navy tour to 5 years or less (flight surgeon tour/separate or civilian deferment/separate). The civilian throughout scenario had the highest net FV of 19, 974, 673 after retiring at the age of 65. Flight surgeon tour/separate and civilian deferment/separate scenarios only made 843, 751 and 1, 401, 630 less respectively than a pure civilian career due to the tax shelter afforded by the military pay. All Navy retirement scenarios to include Navy throughout, civilian deferment/Navy throughout, flight surgeon tour/Navy throughout resulted in a net FV less than 17, 700, 000. Civilian residency/deferment and retiring in the Navy had the worst net FV among all scenarios. Conclusions: It was found that the shorter tours in the Navy had a higher net FV than those who made the Navy a career in orthopedic surgery. Flight surgery is a rewarding operational experience with among the highest net FV among Navy scenarios and is only slightly less than the net FV of a pure civilian career. However, it can be more difficult to apply for civilian orthopedic surgery after serving a flight surgeon tour. Lastly, the net FV was very similar between a civilian orthopedic surgeon career and the shorter tours served in the Navy. Factors such as higher civilian income with associated loan repayment/signing bonuses makes the civilian orthopedic surgery route the best financial option. This study will help those medical students considering a military versus a civilian career in orthopedic surgery and aid in Department of Defense recruitment/retention.